2021
DOI: 10.3390/insects12050373
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mineral Particle Films and Biomaterials on Guava Fruits and Implications for the Oviposition of Anastrepha obliqua (Macquart) (Diptera: Tephritidae)

Abstract: Anastrepha obliqua (Macquart, 1835) is an important pest of tropical fruits, especially Anacardiaceae and Myrtaceae, in the Americas. The objective of this study was to evaluate the influence of mineral films and biomaterials on the coloring of guava fruits (Psidium guajava L.) and implications for the oviposition of A. obliqua. Before the bioassays, color, firmness characteristics, total soluble solids, pH, and titratable acidity were determined to characterize the maturation stage of the fruits. Pieces of gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…After applying the treatments to the fruits, all films significantly increased the luminosity, only kaolin 607 significantly increased the hue angle, and chroma was differentially affected (Kaolin Surround WP and Kaolin 608 decreased chroma, whereas Kaolin 607 increased chroma compared to the control), thus indicating that the kaolin treatments led to color changes in the grapes. Previous studies on kaolin‐based films applied to grapes and guavas also reported color changes in treated fruits (luminosity, chroma, and color angle) (Da Costa et al., 2021a,b).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…After applying the treatments to the fruits, all films significantly increased the luminosity, only kaolin 607 significantly increased the hue angle, and chroma was differentially affected (Kaolin Surround WP and Kaolin 608 decreased chroma, whereas Kaolin 607 increased chroma compared to the control), thus indicating that the kaolin treatments led to color changes in the grapes. Previous studies on kaolin‐based films applied to grapes and guavas also reported color changes in treated fruits (luminosity, chroma, and color angle) (Da Costa et al., 2021a,b).…”
Section: Discussionmentioning
confidence: 86%
“…The kaolin particles were dispersed in distilled water at 200 g L −1 . Guar gum was added to all treatments at 5 g L −1 to improve the viscosity and stability of the suspensions (Campos et al., 2015; Gao et al., 2020; Da Costa et al., 2021a,b). Kaolin Surround WP was obtained from NovaSource (Phoenix, AZ, USA); kaolin 607 and 608 from Brasilminas (São Paulo, Brazil); and guar gum from Mercadão Natural (São Paulo, Brazil).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil is the third-largest producer of fruits in the world, the seventh-largest producer of guava, and the world's largest producer of red guava. 1 However, Brazilian guava production is mainly destined for the domestic market, as only 0.06% of the production is exported. 2 One of the biggest limitations for exportation is the high perishability of the fruit due to its high metabolic rate and the need for rigorous phytosanitary treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Guava is a tropical and subtropical fruit that stands out for its high nutritional value and flavor. Brazil is the third-largest producer of fruits in the world, the seventh-largest producer of guava, and the world’s largest producer of red guava . However, Brazilian guava production is mainly destined for the domestic market, as only 0.06% of the production is exported .…”
Section: Introductionmentioning
confidence: 99%